The impact of socioeconomic vulnerability on COVID-19 outcomes and social distancing in Brazil - Lins-Filho, Paulo Cardoso (2020)
Objective: To assess the impact and correlation of socioeconomic vulnerability on COVID-19 outcomes and social distancing in Brazil. Methods: The Gini Coefficient (GC), the Social Vulnerability Index (SVI), epidemiological data on COVID-19 epidemic in Brazil, and the Social Distancing Index (SDI) were retrieved from online databases and assessed for each Brazilian state. Data was statistically analyzed through non-parametric tests and multiple linear regressions. Results: The mean values for the GC and SVI were 0.495 and 0.261, respectively. A positive statistically significant correlation between the socioeconomic indicators and the three variables related to the COVID-19 outbreak was found. States with very low social vulnerability presented fewer deaths per 100 thousand inhabitants due to COVID-19 than states with moderate social vulnerability. SVI was a predictor of accumulated cases, confirmed deaths, and social distancing in Brazilian states during COVID-19. Conclusions: The COVID-19 outcomes and SDI in Brazilian states are correlated to the socioeconomic condition. The pandemic impacts are more severe in less favored communities.